Features of technical and tactical combinations in competitive kickboxing - Mironov, A.O.; Gerasimov, M.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the specific nature of technical and tactical combinations in kickboxing under situational conditions of competitive activity. Methods and structure of the study. By means of the observation method, indicators were recorded for three categories of technical actions reflecting the level of situational and motor skills of kickboxers: hand strikes, kicks and defensive actions. The recorded data were entered into a special observation protocol, the form and structure of which were determined by the tasks, subject and aims of the study. Results and conclusions. It has been established that the success of kickboxers’ competitive activity is determined both by their technical and tactical training in the course of preparation, and by the influence of certain situational conditions arising during a competitive bout. The structuring of seven factors of competitive activity determines the directions for improving the situational effectiveness of kickboxing athletes.